KELANGSUNGAN HIDUP DAN PERTUMBUHAN LARVA IKAN BETOK (Anabas testudineus) YANG DIBERI CACING SUTERA DIKOMBINASI DENGAN PAKAN BUATAN - Irsyah Rahmi; yulisman .; muslim . (Universitas Sriwijaya, 2016)
ABSTRACT The Problems of climbing perch hatchery are low survival and growth rate in larvae. This is associated with the larvae ability to receive feed transition from the endogenous feeding to the exogenous feeding. During this period, feed must be consistent with required by the larvae either natural feed, artificial feed, or a combination. Naturaly silk worms is given, however availability silk worms is very limited in the wild. There to need to combine silk worms with artificial feed. The purpose of this study is to determine growth and survival rate of climbing perch larvae which is fed silk worms combined with artificial feed. The research had been conducted in Laboratorium Dasar Perikanan, Department of Aquaculture, Agriculture Faculty, Sriwijaya University on January until March 2016. The research method used a completely randomized design with five treatments and three replications. The treatments were P1 (silk worms 100% + 0% artificial feed), P2 (silk worms 75% + 25% artificial feed), P3 (silk worms 50% + artificial feed 50%), P4 (silk worms 25% + 75% artificial feed) and P5 (silk worms 0% + 100% artificial feed). Parameters that had been observed were survival rate, specific growth rate, and water quality parameters. The results showed that culture of climbing perch larvae fed silk worms, artificial feed and combination of them gave significant effect on survival rate and specific growth rate (weight and length). The treatment P3 resulted highest of survival rate 88.67% and specific growth rate (weights 20.16%.days-1 and length 8.11%.days-1). During theÂ research, water quality were in tolerance range for climbing perch larvaeÂ rearing: temperature wasÂ 27-29 oC, pH 6.2-7.3, DO 4.11-5.50 mg.L-1, ammonia 0.01-0.21 mg.L-1. Key words: Climbing perch larvae, Silk worm, Artificial feed, Specific growth rate, Survival rate.